Antidiarrheal activity of the extracts of Valeriana jatamansi Jones on castor oil-induced diarrhea mouse by regulating multiple signal pathways. (15th November 2022) - Ma, Yu-Lei; Wu, Zi-Mei; Liu, Xiao; Lan, Jiang-Er; Zai, Wen-Jing; Jin, Xin; Xie, Hui; Mu, Qing; Liu, Hong-Rui
Abstract: Ethnopharmacological relevance: Valeriana jatamansi Jones, a traditional medicine, is used for various medicinal purposes worldwide. This species is popular for its gastro-protective properties and has been verified to exert antidiarrheal effects. Qiuxieling mixture, an oral liquid preparation used to treat diarrhea in children in clinical practice, was extracted from V. jatamansi Jones. Aim of the study: Although Qiuxieling mixture has a good preventive effect on diarrhea children, the disgusting smell makes it intolerable. Therefore, we extracted odorless products from V. jatamansi Jones and Qiuxieling mixture. The present study is aimed to investigate the protective effects of two ethanolic extracts of V. jatamansi Jones and Qiuxieling mixture against castor oil-induced diarrhea and their possible mechanisms in mice. Materials and methods: The two extracts of V. jatamansi Jones and Qiuxieling mixture were detected by HPLC. A castor oil-induced diarrheal model was used to evaluate the antidiarrheal effects. The expression of Occludin in the small intestine was measured by IHC. Western blotting and immunofluorescence were used to detect the expression of proteins related to the oxidative stress and GSDMD-mediated pyroptosis signaling pathways. ELISA was used to detect the expression of IL-6 and IL-1β in the small intestine of mice with diarrhea. Results: The two extracts of V. jatamansi Jones and Qiuxieling mixture dose-dependently reduced the diarrhea index and the diarrhea rate, delayed the onset of diarrhea, and decreased the weight of the intestinal content. Meanwhile, they reversed the decreased expression of Occludin and restored the activity of Na + -K + -ATPase in the intestines of diarrheal mice. In addition, they reversed the depletion of GSH, attenuated the activation of the ERK/JNK pathway, promoted the Nrf2/SOD1 signaling pathways, and decreased the release of ROS in the intestines of diarrheal mice. Moreover, they suppressed GSDMD-mediated pyroptosis by downregulating the NLRP3/caspase-1/GSDMD signaling pathway. Conclusions: The two extracts of V. jatamansi Jones and Qiuxieling mixture exerted protective effects on castor oil-induced diarrhea in mice through a variety of mechanisms, including antioxidant stress, restoration of tight junctions between intestinal mucosal cells and regulation of the GSDMD-mediated pyroptosis pathway. Graphical abstract: Image 1 Highlights: Two extracts of V. jatamansi Jones and Qiuxueling mixture had no or less disgusting smell compared with Qiuxueling mixture. Two extracts of V. jatamansi Jones and Qiuxueling mixture ameliorated castor oil-induced diarrhea in mice. Two extracts of V. jatamansi Jones and Qiuxueling mixture alleviated castor oil-induced oxidative stress and pyroptosis.